Restructuring a State Nutrition Education and Obesity Prevention Program: Implications of a Local Health Department Model for SNAP-Ed. Issue 1 (January 2017) - Wu, Helen W.; Backman, Desiree; Kizer, Kenneth W.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Context and Objective: The US Department of Agriculture Supplemental Nutrition Assistance Program-Education (SNAP-Ed) funds state programs to improve nutrition and physical activity in low-income populations through its Nutrition Education and Obesity Prevention grants. States vary in how they manage and structure these programs. California substantially restructured its program in 2012 to universally position local health departments (LHDs) as the programmatic lead in all jurisdictions. This study sought to determine whether California's reorganization aligned with desirable attributes of decentralized public management. Design, Setting, and Participants: This study conducted 40 in person, semistructured interviews with 57 local, state, and federal SNAP-Ed stakeholders between October 2014 and March 2015. Local respondents represented 15 counties in all 7 of California's SNAP-Ed regions. We identified 3 common themes that outlined advantages or disadvantages of local public management, and we further defined subthemes within: (1) coordination and communication (within local jurisdictions, across regions, between local and state), (2) efficiency (administrative, fiscal, program), and (3) quality (innovation, skills). We conducted qualitative content analysis to evaluate how respondents characterized the California experience for each theme, identifying positive and negative experiences. Results: California's LHD model offers some distinct advantages, but the model does not exhibit all the advantages of decentralized public management. Strategic planning, partnerships, subcontracting, and fiscal oversight are closer to communities than previously. However, administrative burden remains high and LHDs are limited in their ability to customize programs on the basis of community needs because of state and federal constraints. Conclusions: California's use of a universal LHD model for SNAP-Ed is novel. Recent federal SNAP-Ed changes present an opportunity for other states to consider this structure. Employing small-scale approaches initially (eg, pilot efforts) may facilitate effective transitions. For an LHD model to be effective, LHDs must be adept at managing administrative complexity and capable of succeeding within stringent federal/state requirements.